Beitrag zu einer universellen Baggerschnittstelle zur Übertragung elektrischer und hydraulischer Leistung sowie elektronischer Signale für komplexe Anbaugeräte - Schwab, Christian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2014)
Excavators provide a big variety of tasks with specialized accessory attachments. If the number of hydraulic functions however is too high or the function requires an exact control a manual control is not possible. This thesis presents a control system for excavator accessory attachments which enables the control of complex accessory attachments.